Pengaruh Intensitas Penggunaan Media Sosial dengan Ruminasi Pada Gen Z - Syahida, Kafa Billahi; Hariyono, Dyta Setiawati; Marsha, Gladis Corinna (Universitas Pahlawan Tuanku Tambusai, 2025)
Social media and the internet are the main platforms for Gen Z to communicate and share information. The use of social media has positive and negative impacts on its users. Frequent and repeated use of social media will create intensity of use. Social media can be related to rumination. Rumination is repeated contemplation of problems or negative feelings and referring to the meaning of the problem. Individuals who tend to ruminate are more likely to experience more severe depressive episodes. This study is useful for providing definitive data in seeing the effect of the intensity of social media use on rumination in Gen Z. Sampling in this study used non-probability sampling with a purposive sampling technique with a sample size of 85 participants. The data analysis method used one way ANOVA. The results of this study obtained a significant effect on the level of rumination based on the intensity of social media use in Gen Z with a p value <0.001.